PISA XALQARO BAHOLASH DASTURI VA DASTUR DOIRASIDA O’QUVCHILARNING KREATIV FIKRLASHINI BAHOLASH - Sh.Ibragimova, X. (SCIENCE and SOCIETY, 2021)
This article deals with the origins of the origins of the PISA International Assessment Program, its role in the world community, works done through the PISA program, achieved results, and it also discusses about developing the creative thinking evolving in PISA research.